A Novel Approach to Measure the Chip Formation Temperature Using the Implanted Thermocouple Method - Silva, C. P. P.; Oliveira, T. C. C.; Lisboa, R. G.; Da Silva, M. B.; Abrão, A. M.; da Silva, R. H. L.; Pereira, I. C. (Experimental techniques (Westport, Conn.), 2024)
Simultaneous measurement of the temperature in different regions during machining operations presents many limitations. Currently, only orthogonal cutting using a infrared camera allows the simultaneous measurement of temperature in different regions. Additionally, temperature measurement in certain regions is a challenge, for instance, in the chip/tool interface and inside the chip. The application of advanced sensors and the adaptation of well-established techniques in regions of difficult access, such as the chip-tool interface and the chip itself, have been the subject of research to allow the better understanding of the heat generation and temperature evolution during machining operations. This work investigates the application of the inserted thermocouple method to measure the temperature inside the chip during its formation, together with the tool-workpiece thermocouple method to compare the effect of the cutting parameters on both the chip-tool interface and chip temperature. Orthogonal cutting of AISI 1020 steel was performed using cemented tungsten carbide bits. The findings indicated that both methods were able to assess the influence of the investigated parameters and that temperature presented the same behavior, in spite of the differences in absolute values (higher temperatures were recorded using the tool-workpiece thermocouple). Temperature increased with cutting speed, decreased with the elevation of the undeformed chip thickness and was not affected by width of cut. The highest temperature (668 °C) was observed at the tool-workpiece interface using a cutting speed of 120 m/min, undeformed chip thickness of 0.1 mm and width of cut of 1.5 mm.